Ocrelizumab reduces thalamic volume loss in patients with RMS and PPMS. (October 2022) - Arnold, Douglas L; Sprenger, Till; Bar-Or, Amit; Wolinsky, Jerry S; Kappos, Ludwig; Kolind, Shannon; Bonati, Ulrike; Magon, Stefano; van Beek, Johan; Koendgen, Harold; Bortolami, Oscar; Bernasconi, Corrado; et al.
Background: In multiple sclerosis (MS), thalamic integrity is affected directly by demyelination and neuronal loss, and indirectly by gray/white matter lesions outside the thalamus, altering thalamic neuronal projections. Objective: To assess the efficacy of ocrelizumab compared with interferon beta-1a (IFNβ1a)/placebo on thalamic volume loss and the effect of switching to ocrelizumab on volume change in the Phase III trials in relapsing MS (RMS, OPERA I/II; NCT01247324/NCT01412333) and in primary progressive MS (PPMS, ORATORIO; NCT01194570). Methods: Thalamic volume change was computed using paired Jacobian integration and analyzed using an adjusted mixed-effects repeated measurement model. Results: Over the double-blind period, ocrelizumab treatment significantly reduced thalamic volume loss with the largest effect size (Cohen's d : RMS: 0.561 at week 96; PPMS: 0.427 at week 120) compared with whole brain, cortical gray matter, and white matter volume loss. At the end of up to 7 years of follow-up, patients initially randomized to ocrelizumab still showed less thalamic volume loss than those switching from IFNβ1a ( p < 0.001) or placebo ( p < 0.001). Conclusion: Ocrelizumab effectively reduced thalamic volume loss compared with IFNβ1a/placebo. Early treatment effects on thalamic tissue preservation persisted over time. Thalamic volume loss could be a potential sensitive marker of persisting tissue damage.